Considering "Nonlinearity" Across the Continuum in Medical Education Assessment: Supporting Theory, Practice, and Future Research Directions. Issue 3 (2015) - Durning, Steven J.; Lubarsky, Stuart; Torre, Dario; Dory, Valérie; Holmboe, Eric
Abstract : N/A: The purpose of this article is to propose new approaches to assessment that are grounded in educational theory and the concept of "nonlinearity." The new approaches take into account related phenomena such as "uncertainty, " "ambiguity, " and "chaos." To illustrate these approaches, we will use the example of assessment of clinical reasoning, although the principles we outline may apply equally well to assessment of other constructs in medical education. Theoretical perspectives include a discussion of script theory, assimilation theory, self‐regulated learning theory, and situated cognition. Assessment examples to include script concordance testing, concept maps, self‐regulated learning microanalytic technique, and work‐based assessment, which parallel the above‐stated theories, respectively, are also highlighted. We conclude with some practical suggestions for approaching nonlinearity.